Determinants of child sex ratio in West and South Districts of Tripura, India - Himadri Bhattacharjya; Subrata Baidya (Wolters Kluwer Medknow Publications, 2017)
Background: Indian census 2011 has detected declined child sex ratio in the West and South districts of Tripura State. Objectives: To find out the sex ratio at birth and to identify the factors affecting child sex ratio in west and south districts of Tripura. Methods: This community-based cross-sectional study combined with a qualitative component was conducted among 3438 couples chosen by multistage sampling. Quantitative data were collected by a structured interview schedule. Data were analyzed by computer using SPSS version 15.0. Chi-square test was applied for testing the significance of study findings and P < 0.05 was considered statistically significant. Qualitative data were collected by Focus Group Discussions and analyzed by qualitative free listing and pile sorting considering Smith's S value. Results: Sex ratio at birth in West and South Tripura districts during 2013 was found to be 972 and 829 respectively. Son preference was higher among couples irrespective of their literacy, residence, occupation, family type and religion except Christianity. Expenditure at marriage, lesser contribution to parent's family and fears of adverse situations at in law's house after marriage etc. were causes for lesser daughter preference. Very few pregnant women underwent ultrasonography for sex determination of fetus. Girls had differential or delayed medical care and higher death rate. The desire for children was found to be limited after male births. Conclusions: Low daughter preference was mostly due to economic reasons and prolonged contraception following male birth. Literacy, occupation and residence of study subjects did not modify prevalent higher male preference.